SOURCES AND PROVENANCES OF LOWER PROTEROZOIC TERRIGENOUS ROCKS OF THE UDOKAN GROUP, SOUTHERN KODAR-UDOKAN DEPRESSION: RESULTS OF SM-ND ISOTOPIC INVESTIGATIONS - Podkovyrov V.N.; Kotov A.B.; Larin A.M.; Kotova L.N.; Kovach V.P.; Zagornaya N.Yu. (My University, 2006)
The Early Proterozoic was characterized by the development of large epicratonic depressions, which often host large and unique deposits of Cu, Pb, Zn, U, Au, Fe, phosphorites, barite, fluorite, and other mineral resources. In the western part of the Aldan shield, such structures are represented by Early Proterozoic Udokan-type depressions (Kodar–Udokan Depression and Ugui, Oldongso, and Lower Khani graben-synclines). The Kodar–Udokan Depression, the largest epicratonic structure, hosts the unique stratiform deposits of cupriferous sandstones. This depression is located in the southern part of the Chara–Olekma geoblock at the boundary with the Stanovoi suture zone and is composed of the Kodar and Udokan subzones, which are separated by the Chara Depression.
Keywords: Kodar–Udokan depression; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой